Anti-inflammatory loading of cinnamaldehyde on artificial bone scaffolds against the process of bone regeneration - Dewi, Anne Handrini; Triawan, Andi; Jansen, John (Majalah Kedokteran Gigi Indonesia, 2023)
Cinnamaldehyde is an organic component in cinnamon and has anti-inflammatory, antibacterial, and osteogenic properties. Loading cinnamaldehyde with a concentration of 4% into an artificial scaffold from gypsum calcium carbonate hydrogel could reduce inflammation, accelerate healing, and promote new bone regeneration at bone implantation surgery. The aim of this study was to investigate the impact of cinnamaldehyde loaded on gypsum-hydrogel calcium carbonate on the process of wound healing and bone regeneration in rats. Implantation of bone scaffolding from gypsum hydrogel calcium carbonate with an addition of cinnamaldehyde was performed on 20 5-month-old Sprague-Dawley rats weighing 300-350 g in an artificial defect of condyle femoris bone dexter and sinister. Group A was a control with gypsum only, while groups B, C, and D were given gypsum and CaCO3 with a combination of cinnamaldehyde or dehydrothermal treatment (DHT). Euthanasia was performed after implantation at 1, 4 and 8 weeks for 4 groups (n = 3). Femoris condyle bone was cut, made into histological preparations by hematoxylin eosin (HE) staining, and analyzed descriptively. The results showed that the loading of cinnamaldehyde on the scaffold was effective in weeks 1 and 4, but after 8 weeks of implantation, cinnamaldehyde was observed to inhibit defect closure. The cinnamaldehyde group combined with dehydrothermal (DHT) treatment was found to be better than those without DHT.